Can previous use of benzodiazepines, Z-drugs, and opioids predict incident pregabalin use? - Sveinn Hlynur Tómasson 1998- (2023)
Background: Pregabalin is a gabapentinoid indicated for the treatment of epilepsy, neuropathic pain, and general anxiety disorder. Off-label use of pregabalin is common, and its potential for abuse, especially with opioids and benzodiazepines has been the topic of several studies, but few such studies have been performed in Iceland. Aim: The aim of this study was to determine whether there is a relationship between previous use of benzodiazepines, Z-drugs, and opioids and incident pregabalin use with special consideration for the conditions pregabalin is indicated to treat. Methods: This was a retrospective cohort study, using data from the Primary Healthcare of the Capital Area in Iceland and the Icelandic Medicines Registry to analyze the drug use of the study population (n= 105,631). It comprised individuals 10-69 years old, attending primary healthcare in the capital area of Iceland between the years 2009 to 2012. The population was divided into four groups based on their past drug use and each group’s incidence rate ratio for pregabalin use analyzed using Cox proportional hazard regression. Results: Previous use of benzodiazepines/Z-drugs resulted in an incidence rate ratio of 4.17 (95% CI, 3.58-4.86) for pregabalin use, for previous use of codeine/tramadol, the incidence rate ratio was 3.46 (95% CI, 2.93-4.07), and for previous use of both benzodiazepines/Zdrugs and codeine/tramadol it was 8.13 (6.91-9.57). Conclusion: Previous use of benzodiazepines, Z-drugs, and opioids led to an increased incidence risk ratio for pregabalin use in the study population. It was also associated with using higher doses of pregabalin as well as longer duration of use. These effects also appeared to be dose dependent, except in those who only use codeine/tramadol. Bakgrunnur: Pregabalín er gabapentínóíð með ábendingu sem meðferð við flogaveiki, taugaverkjum, og almennri kvíðaröskun. Notkun pregabalíns utan skráðra ábendinga er algeng og misnotkun þess, þá sérstaklega með ópíóíðum og benzódíazepínum hefur verið viðfangsefni ...